1995
DOI: 10.1074/jbc.270.48.29004
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization and Internalization of the m2 Muscarinic Acetylcholine Receptor Are Directed by Independent Mechanisms

Abstract: The phenomenon of acute desensitization of G-protein-coupled receptors has been associated with several events, including receptor phosphorylation, loss of high affinity agonist binding, receptor:G-protein uncoupling, and receptor internalization. However, the biochemical events underlying these processes are not fully understood, and their contributions to the loss of signaling remain correlative. In addition, the nature of the kinases and the receptor domains which are involved in modulation of activity have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
123
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 56 publications
11
123
1
Order By: Relevance
“…This K220R mutant of GRK2 cannot perform a phosphotransferase reaction (35); therefore, for any receptor substrate of GRK2, the K220R mutant can act as a competitive inhibitor of any GRK that could bind to and subsequently phosphorylate the receptor (18,21,(35)(36)(37). Characteristically, however, the GRK2 K220R mutant inhibits GRK action incompletely; even when present in 15-fold molar excess over GRK2, the K220R mutant inhibits only 60% of agonist-stimulated ␤ 2 -adrenergic receptor phosphorylation in vitro (35).…”
Section: Resultsmentioning
confidence: 99%
“…This K220R mutant of GRK2 cannot perform a phosphotransferase reaction (35); therefore, for any receptor substrate of GRK2, the K220R mutant can act as a competitive inhibitor of any GRK that could bind to and subsequently phosphorylate the receptor (18,21,(35)(36)(37). Characteristically, however, the GRK2 K220R mutant inhibits GRK action incompletely; even when present in 15-fold molar excess over GRK2, the K220R mutant inhibits only 60% of agonist-stimulated ␤ 2 -adrenergic receptor phosphorylation in vitro (35).…”
Section: Resultsmentioning
confidence: 99%
“…Many G protein-coupled receptors become phosphorylated in response to agonist stimulation (Palmer et al, 1995;Pals-Rylaarsdam et al, 1995;Pippig et al, 1995;Heurich et al, 1996), and this modification has been linked to the functional desensitization of the receptor (Pippig et al, 1995;Garland et al, 1996). Furthermore, subsequent dephosphorylation of the receptor by protein phosphatases may play a role in receptor resensitization (Krueger et al, 1997).…”
Section: Role Of Receptor Dephosphorylation In Resensitizationmentioning
confidence: 99%
“…However, loss of receptors from the surface is often too slow to account for the rapid onset of desensitization (Roth et al, 1991;Tobin et al, 1992;Fisher et al, 1994), and the effects of site-directed mutations on receptor internalization and desensitization are often disparate (Barak et al, 1994;Pals-Rylaarsdam et al, 1995), suggesting that the major functional role of internalization is not simply to cause desensitization. An alternative hypothesis is that receptor cycling is involved in receptor resensitization (Yu et al, 1993).…”
mentioning
confidence: 99%
“…40), the data in this manuscript support the hypothesis that, following stimulation by agonist, cardiac m2 mAchR translocation to caveolae may be necessary to initiate specific downstream signaling cascades. Interestingly, several recent studies have shown that internalization of the m2 and m4 mAchR is mediated by mechanisms distinct from the phosphorylation by the G protein-coupled receptor kinase (GRK) family known to lead to receptor desensitization (41,42). The translocation of muscarinic receptors within caveolae should allow their interaction with the heterotrimeric G protein complexes known to be concentrated within these plasmalemmal microdomains (12,26,28) and lead, after recruitment of co-factors and intermediate effector proteins, to the activation of eNOS, a resident caveolar protein in cardiac myocytes.…”
Section: Agonist-induced Targeting Of Muscarinic Cholinergic Receptormentioning
confidence: 99%